SOCIAL MEDIA FOR IMPROVING STUDENTS’ ENGLISH QUALITY IN MILLENNIAL ERA - Azizah Maulina Erzad; Suciati Suciati (Edulingua: Jurnal Linguistiks Terapan dan Pendidikan Bahasa Inggris, 2018)
In millennial era, many young generations use social media for various purposes. One of them is for improving their English quality. This study aims to know the social media applications mostly used by the students, the English skills can be improved and the reasons why they use social media for improving English quality in millennial era. The participants are30 students of Class B, second semester of English Education Department in IAIN Kudus. In collecting data, this qualitative research used observation, interview and documentation. Based on the data, there are three results. First, the social media applications mostly used by the students are youtube, instagram, facebook, and line. Second, the students’ English skills can be improved by social media in order are listening, speaking, writing and reading. And, they use social media for improving English quality in millennial era because it isfun, interesting, easy to use/access, effective, simple and informative.